ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730)

Planung von Wärmepumpen für die kommunale Wärmeversorgung - Divkovic, Denis; Schlosser, Florian

Kommunale Wärmeplanung - Divkovic, Denis; Schlosser, Florian

Responsibility Assignment in Systems Engineering - Gräßler, Iris; Thiele, Henrik; Grewe, Benedikt; Hieb, Michael (Proceedings of the Design Society)
Abstract Increasing system complexity can be controlled by using systems engineering processes. INCOSE defines processes with inputs and outputs (artifacts) for this purpose. Specific SE roles are used to organize the tasks of the processes within the company. In this work, the responsibilities for artifacts are evaluated by means of the RACI scheme and examined by a cluster analysis and discussed for a SE transformation project with a German automotive OEM. As a result of the study, the optimal composition for systems engineering teams is identified and the systems engineering roles are prioritized.
Keywords: systems engineering (SE); project management; model-based systems engineering (MBSE)

Investigation on future district heating systems for German cities with existing district heating network - Divkovic, Denis; Knorr, Lukas; Meschede, Henning

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen. Eine qualitative Studie über Informations- und Unterstützungsbedarfe von jungen Familien in Deutschland. - Wicker, Kathrin

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen - Wicker, Kathrin

Supporting Geometry Learning Digitally-an Interdisciplinary Project to Foster Spatial Competences and Individual Learning Paths by Using Adaptable Algorithmic Feedback Capabilities - Winkelnkemper, Felix; Huhmann, Tobias; Bechinie, Dominik; Eilerts, Katja; Lenke, Michael; Schulte, Carsten (Society for Information Technology & Teacher Education International Conference)
Keywords: ⛔ No DOI found

Digitalisierung als Chance und Herausforderung - Bemerkungen aus der Didaktik der Informatik - Schulte, Carsten; Winkelnkemper, Felix (Theologie im Übergang - Identität - Digitalisierung - Dialog)

SUPPORTING GEOMETRY LEARNING DIGITALLY THROUGH ADAPTABLE ALGORITHMIC FEEDBACK-CHALLENGES AND SOLUTIONS - Huhmann, Tobias; Winkelnkemper, Felix (EDULEARN22 Proceedings)

Pentomino Digital - Mit Einer App Geometrie Lernen - Huhmann, Tobias; Eilerts, Katja; Winkelnkemper, Felix (Mathematik differenziert)
Keywords: ⛔ No DOI found

Multiscale analysis of composite structures with goal-oriented mesh adaptivity and reduced order homogenization - Ju, Xiaozhe; Mahnken, Rolf; Xu, Yangjian; Liang, Lihua; Cheng, Chun; Zhou, Wangmin (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Ausbildung in der zweiten Phase der Lehrerbildung. - Tenberge, Claudia (Professionalisierung von Grundschullehrkräften.)

Holz erleben. Technik verstehen. - Möller, Kornelia; Eikmeyer, Birgit; Tenberge, Claudia; Wilke, Torben; Zolg, Monika

Modeling Concepts for Reactive Separations - Kenig, Eugeny (Process Intensification by Reactive and Membrane-Assisted Separations)

Effect of diffusivity and chemical reactions on the determination of mass transfer coefficients in columns with structured packing - Mapura, Luz Alejandra; Kenig, Eugeny Y. (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Experimental study on the condensation of pure substances in outer pillow-plate channels - Buckmann, Felix; Kenig, Eugeny (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Heat regeneration model for external heat engines operating with dense working fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny Y. (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Begleitforschungsseminare - Frust oder Lust, Pflicht oder Kür? - Jonas-Ahrend, Gabriela; Temmen, Katrin